Analysis Traffic Volume of Rigid Pavement Damage on Roads Badami Karawang - Abiansyah, Lutfi; Rifai, Andri Irfan (Journal of World Conference (JWC), 2020)
The road was a means of land transport is very important to the social relations and economic goods and services, and with a population that is increasing in every year to year, increasing the number of vehicles passing on the road that there is, therefore, in need planning a safe way according to the function, volume, and nature of traffic. Road repairs cost a lot and this action is felt not quite right because remedies can not survive by age plans and in kutif of IDN Times in 2019 that the condition damages the highway in the district of Karawang based on data from the Department of Public Works and Spatial Planning (PUPR) Khanewal district, along with the road status 1937.53 kilometers of district roads in poor condition. (IDN Times, 2019). This study was conducted to assess how much influence the volume of vehicles to the damage occurred on roads Badami karawang at STA 0 + 000-0 + 500 and STA 2 + 250-2 + ??750, to examine the above problems by analyzing data from LHR and road damage the method of Highways, then further by looking at the correlation between the volume of vehicles on the road destruction by using SPSS and to increase the strength of rigid pavement using cement concrete road pavement planning 2003 is an additional layer (overlay) using the rigid pavement. From the analysis and discussion get Simultaneous Effect Hypothesis Test results that the Sig. (0,000) <? (0.05) and f count (35.671)> F table (3.89) H0 is rejected. It can be concluded that the simultaneous effect of the Light Vehicle Road damage of 33.8%, the simultaneous effect of the Heavy Vehicle Road damage amounted to 47.7%, Motorcycles simultaneous effect on road damage by 12.1% and the simultaneous effect of Motor Vehicles not to road damage by 14.2%, the result of the identification of the type and class of road damage indicates that the need for administration of additional layer (overlay) as a treatment for damage to roads, based on the analysis of the design used road repair method with a design life of 10 years, namely: (Overlay) Rigid Pavement (Rigid Pavement) as thick as 18 cm .and of analysts earn fees at cost (overlay) Rigid Pavement (Rigid Pavement) Rp. 9,114,626,20 / segments.